The Role of Informal Controls and a Bargaining Opponent's Emotions on Transfer Pricing Judgments - Bhattacharjee, Sudip; Moreno, Kimberly K. (Contemporary Accounting Research, 2017)
Abstract While accounting research has demonstrated the role of a decision maker's own emotions during judgments, psychology research proposes that others’ emotions provide an informational signal to assess an opponent's limits, cooperativeness, and toughness during bargaining. We examine how a bargaining opponent's emotions provide information signals that can be used by a selling division manager during transfer pricing decisions and whether informal control system choices by corporate management to foster cooperation can create a context that influences how managers react to these signals. In an experiment, when informal controls to encourage cooperation were absent (less collaborative environment), managers’ selling price estimates were more conciliatory when the opponent was described as displaying negative emotions than when described as displaying positive emotions. However, when informal controls to cooperate were present (more collaborative environment), managers’ selling price estimates were more conciliatory when the opponent displayed positive rather than negative emotions. Path analyses suggest that managers’ perception of their opponents’ signals is the mechanism by which opponents’ emotions influence transfer‐price decisions. This study highlights the role of others’ emotions as information signals during accounting bargaining and provides insight into the context dependency of opponents’ emotions under various control system structures.